Caroline Bynum and Medieval Art History in America: Perspectives from an Art Historian and Student - Jung, Jacqueline E. (Common knowledge, 2024)
As a contribution to the Common Knowledge symposium "Caroline Walker Bynum across the Disciplines," this essay stresses Bynum's commitment to the methods and questions of history but also the unparalleled impact of her work on adjacent fields, including and perhaps even especially art history. Furthermore, her body of scholarship registers a consistent engagement with art historians. Weaving together personal memoir and historiography, this article sketches the manifold ways in which Bynum's publications have responded to and shaped the contours of medieval art history in America since the early 1990s—particularly with respect to questions of gender, body, identity, violence, and materiality—and the formative role that her mentorship and pedagogy have played in the author's development as an art historian.